Fungsi Dan Layanan Ekosistem Sungai Banjaran, Purwokerto, Jawa Tengah - Isnaeni, Bekti (BIOMA: Jurnal Biologi dan Pembelajarannya, 2025)
One of the rivers located in the Purwokerto area, Central Java, is the Banjaran River, which contains ecosystem services. The Banjaran River is used by the local community for their daily needs. Research on the functions and services of the Banjaran River ecosystem has never been conducted. The purpose of this study is to determine the functions and services provided by the Banjaran River ecosystem. This study used a descriptive method with purposive sampling technique. The results showed that the ecosystem functions and services found in the Banjaran River include supporting services, which provide habitat for gastropods and act as litter feeders; provisioning services, as evidenced by the presence of gastropods as a food source and the availability of water sources; and regulation and maintenance (microclimate) services, as evidenced by the temperature and humidity of the area around the river.